2013
DOI: 10.5047/eps.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Barometric and magnetic observations of vertical acoustic resonance and resultant generation of field-aligned current associated with earthquakes

Abstract: Three rare occasions are introduced, where the excitation of vertical acoustic resonance between the ground and the ionosphere, and the resultant generation of a field-aligned current, just after earthquakes are observationally confirmed. In the case of two inland earthquakes, barometric observations very close to the epicenters (i.e., only 30 km apart) were available, and they showed a sharp spectral peak which appeared within one hour after the origin time and lasted a few hours. The observed periods of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
4
13
0
Order By: Relevance
“…Four-minute geomagnetic and/or barometric oscillations after the 2004Sumatra, 2007Mieken-Chubu, 2008 Iwate-Miyagi Nairiku, and 2010 Chile earthquakes were observed in previous studies (Iyemori et al 2005(Iyemori et al , 2013. Previous researchers have claimed that the acoustic waves propagated vertically to the ionosphere and were reflected back to the ground.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Four-minute geomagnetic and/or barometric oscillations after the 2004Sumatra, 2007Mieken-Chubu, 2008 Iwate-Miyagi Nairiku, and 2010 Chile earthquakes were observed in previous studies (Iyemori et al 2005(Iyemori et al , 2013. Previous researchers have claimed that the acoustic waves propagated vertically to the ionosphere and were reflected back to the ground.…”
Section: Introductionmentioning
confidence: 85%
“…That is, the vertical acoustic resonances occurred after the earthquakes, and generated an ionospheric dynamo above the epicenter (see Fig. 11 in Iyemori et al 2013). The numerical simulation performed in Zettergren et al (2017) supports these observations.…”
Section: Introductionmentioning
confidence: 99%
“…5b. Note that the 4-min geomagnetic fluctuation just after the 2010 Chile earthquake was only seen in D components (Iyemori et al 2013) probably because it occurred in midnight when the ionospheric conductivity, in particular the Cowling conductivity, was low. These spectral peaks are close to the theoretical periods of the VAR between the ionosphere and the ground, i.e., 260-280, 220-230 and around 200 s. The relatively large amplitude variations before the eruption (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After volcanic eruption (e.g., Heki 2006;Dautermann et al 2009) or massive tornado (e.g., Nishioka et al 2013), disturbances in total electron content (TEC) have been observed. After great earthquakes, short-period magnetic and atmospheric pressure oscillations (e.g., Iyemori et al 2005Iyemori et al , 2013 or TEC variations (e.g., Otsuka et al 2006;Saito et al 2011) were observed. As to the theoretical study, TEC oscillations observed after the 2011 off the Pacific coast of Tohoku Earthquake and FACs in the ionosphere generated by acoustic mode waves were well reproduced with numerical simulations by Matsumura et al (2011) and by Zettergren and Snively (2013), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…After the devastating 2004 Indian Ocean Tsunami, scientific communities pay many interests on observing tsunami by ionospheric sounding (Artru et al 2005;Liu et al 2006;Occhipinti et al 2006;Mai and Kiang 2009;Hickey et al 2010;Rolland et al 2010;Galvan et al 2011;Liu et al 2011;Makela et al 2011;Iyemori et al 2013;Occhipinti et al 2013). Due to the high spatial and temporal resolution, total electron content (TEC) derived from ground-based GPS has widely been used as the observations in the studies.…”
Section: Introductionmentioning
confidence: 99%